The pro-regenerative effects of hyperIL6 in drug-induced liver injury are unexpectedly due to competitive inhibition of IL11 signaling - Jinrui Dong (eLife Sciences Publications Ltd, 2021)
It is generally accepted that IL6-mediated STAT3 signaling in hepatocytes, mediated via glycoprotein 130 (gp130; IL6ST), is beneficial and that the synthetic IL6:IL6ST fusion protein (HyperIL6) promotes liver regeneration. Recently, autocrine IL11 activity that also acts via IL6ST but uses ERK rather than STAT3 to signal, was found to be hepatotoxic. Here we examined whether the beneficial effects of HyperIL6 could reflect unappreciated competitive inhibition of IL11-dependent IL6ST signaling. In human and mouse hepatocytes, HyperIL6 reduced N-acetyl-p-aminophenol (APAP)-induced cell death independent of STAT3 activation and instead, dose-dependently, inhibited IL11-related signaling and toxicities. In mice, expression of HyperIl6 reduced ERK activation and promoted STAT3-independent hepatic regeneration (PCNA, Cyclin D1, Ki67) following administration of either IL11 or APAP. Inhibition of putative intrinsic IL6 trans-signaling had no effect on liver regeneration in mice. Following APAP, mice deleted for Il11 exhibited spontaneous liver repair but HyperIl6, despite robustly activating STAT3, had no effect on liver regeneration in this strain. These data show that synthetic IL6ST binding proteins such as HyperIL6 can have unexpected, on-target effects and suggest IL11, not IL6, as important for liver regeneration.